Exploring Negative Career Thoughts Between STEM‐Declared and STEM‐Interested Students. Issue 4 (4th December 2018) - Prescod, Diandra J.; Daire, Andrew P.; Young, Cynthia; Dagley, Melissa; Georgiopoulos, Michael
Abstract : The shortage of science, technology, engineering, and math (STEM) professionals in the United States leaves many available positions unfilled. Students beginning college with declared STEM majors often change majors in college, contributing to retention difficulties. Using the Career Thoughts Inventory (Sampson, Peterson, Lenz, Reardon, & Saunders, 1996a ), the authors examined negative career thoughts between undergraduate STEM‐declared students participating in a STEM retention project and STEM‐interested students participating in a National Science Foundation–funded STEM recruitment and retention project. Results indicated significant differences between the 2 groups, with STEM‐interested students reporting greater negative career thoughts.